Digitalization and the Challenges for the Accounting Profession (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
Accounting profession is traditional profession and accounting rules and principles have been established and are the same for many years. However, globalization of business, stronger regulations and numerous technological solutions and innovations are not bypassing the accounting profession either. Challenges for the accounting profession are reflected in the need for rapid adaptation and transformation of business practice and business processes without abandoning away from basic accounting rules and principles. The aim of this paper is to analyze and systematize the key challenges that digitalization brings for the accounting profession. Research is based on the review of relevant and available professional and academic literature. The results are showing that accounting profession is faced with numerous challenges in the era of digitalization. Key challenges could be systematized in following: the use of big data in accounting and reporting, cloud computing and continuous accounting, artificial intelligence and blockchain technology. The conclusion of this research is that changes in technology and digitalization will have a significant impact on the accounting profession in the coming period. Changes are moving toward reporting on a daily basis, difference on the way of preparing business and strategic plans, implementation of digital wallet and on-line accounting as well as outsourcing of accounting in distant countries. Education system is going to change in circumstances of growing digitalization of business. Also, users of accounting information in digital era are changing; they want accounting information right away when a business event occurs, not with time lag. Those changes will influence on the way accountants carry out their job, it will be necessary the knowledge of new skills especially in engineering, and, finally, that will lead to new types of the accounting professionals.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.